The Influence of Facilities, Accessibility, and Entrance Ticket Prices on Consumer Decisions in Choosing East Java Park 1 Tourist Destinations, Batu City - Cintia Nur Halimatussa’diyah; R.Yuniardi Rusdianto (GLOBAL SCIENTS PUBLISHER, 2024)
This study seeks to assess the impact of amenities, accessibility, and admission fees on consumer choices on the tourism destination of Jawa Timur Park 1 in Batu City. This research employs a quantitative methodology. The study sample comprised 157 individuals who had visited Jawa Timur Park 1. The sample method employed was non-probability sampling using a purposive approach. The data gathering method involved the distribution of questionnaires. The analytical method employed was multiple linear regression analysis. The study's results demonstrate that facilities, accessibility, and entrance ticket prices each exert a positive and significant influence on the decision to visit Jawa Timur Park 1. The facilities, accessibility, and admission ticket prices simultaneously influence the choice to attend Jawa Timur Park 1.